FRI0271 USE OF CONTRAST ENHANCED ULTRASOUND SONOGRAPHY (CEUS) IN LARGE VESSEL VASCULITIS (LVV). (June 2019) - Bergner, Raoul; Splitthoff, Jan; Wadsack, Daniel
Abstract : Background: C-reactive protein (CRP) and erythrocyte sedimentation rate (ESR) are important parameters in the monitoring of LVV. Since Tocilizumab is approved for treatment of LVV these cheap and easy repeatable parameters are worthless because of their normalisation by Tocilizumab. MRI and PET-CT as an alternative are not only much more expensive, they are also not arbitrarily repeatable and available. Thus, monitoring of LVV-Patients undergoing a Tocilizumab therapy remains unclear – especially upon showing a persisting thickened vessel wall. Objectives: CEUS can increase the visibility of tissue perfusion, particularly if there is a very slow bloodflow, which cannot be detected by (power)-doppler sonography. Methods: In this proof of concept study we investigated patients with active and inactive LVV (aLVV/iLVV) with CEUS. After injection of ultrasound contrast agent we measured the contrasted area of large vessels in a transverse section first if the lumen was completely contrasted and once again 4-8 seconds later. If the vessel wall incorporated the contrast agent the contrasted area increased (Fig 1 ). The increase of the contrasted area (CA) was correlated with CRP and ESR. Patients were only included if they were not treated with Tocilizumab and therefore ESR and CRP were usable to evaluate the disease activity. Results: Investigated were 16 patients (13 female, 3 male), 8 with aLVV and 8 with iLVV, respectively. The mean CRP was 85±69 (aLVV) vs. 4±2 mg/l (iLVV) (p<0.0001), the ESR 80±28 (aLVV) vs. 7±4 (iLVV) mm/h (p< 0.0001). The mean age was 74.6±8.4 y (range 56-82). The increase of the CA was 66.6±44.6 (aLVV) vs. 2.4±6.6% (iLVV) (p<0.0001). The increase correlated significantly with the CRP r=0.87, p<0.0001. An increase of CA of ≥20% has a sensitivity of 92, 3% and a specificity of 90% for active LVV. Conclusion: The results of our proof of concept study demonstrate, that CEUS can detect aLVV with a good sensitivity and specificity. Including CEUS in clinical routine will be much easier repeatable, save, quicker and by far more cost-effective then MRI or PET-CT. CEUS might be a good method for monitoring disease activity in LVV treated with Tocilizumab. The limitation of our study is the small number of patients, the missing blinding of the investigator and the method intrinsic fact, that you can't investigate all involved vessels by ultrasound/CEUS. References: None Disclosure of Interests: Raoul Bergner Speakers bureau: Abbvie, Roche, Novartis, Bristol Myers Squibb, Jan Splitthoff: None declared, Daniel Wadsack Speakers bureau: Bristol Myers Squibb